Gender, violence and HIV: women's survival in the streets - Epele, María Esther (2002)
In this article I propose that genderinequality promotes – directly or indirectly –vulnerability to HIV as a consequence of amultidimensional violence (structural, symbolicand physical) experienced by injection drugusing (IDU) women in The Mission District (SanFrancisco). Given the female subordinated positionstipulated by the street ideology, I analyzehow drug dependence afforded by precariousstrategies of subsistence places IDU womenunder multiple dangers and threats. In thissetting, unequal gender relations are part of acomplex system of transactions in the streeteconomy and a way to reduce or increase theeveryday violence. Facing multiple dangers andrisks, some women adopt a subordinatedposition, some try to negotiate the conditionsof the exchanges and the others resist theexploitation. Finally, everyday violence under conditions ofgender inequality and scarcity of resourcesimposes a logic defined by the challenge ofsurvival under the threat of immediate dangers,which transform HIV into a secondary risk.